Human brucellosis and fever of unknown origin - Zhi-guo Wu; Zhi-ying Song; Wei-xin Wang; Wen-na Xi; Di Jin; Mao-xing Ai; Yu-chan Wu; Yu Lan; Shu-fen Song; Gong-chang Zhang; Xue-bing Yao; Zhen Gao; et al. (BMC Infectious Diseases, 2022)
Abstract Background Human brucellosis has become one of the major public health problems in China, and increases atypical manifestations, such as fever of unknown origin (FUO), and misdiagnosis rates has complicated the diagnosis of brucellosis. To date, no relevant study on the relationship between brucellosis and FUO has been conducted. Methods We retrospectively reviewed the medical charts of 35 patients with confirmed human brucellosis and prospectively recorded their outcomes by telephone interview. The patients were admitted to the Second Affiliated Hospital of Nanchang University between January 01, 2013 and October 31, 2019. Patient data were collected from hospital medical records. Results The percentage of males was significantly higher than that of female in FUO (78.95% vs. 21.05%, P < 0.05), and 80% of the patients had a clear history of exposure to cattle and sheep. Moreover, 19 (54%) cases were hospitalized with FUO, among which the patients with epidemiological histories were significantly more than those without (P < 0.05). The incidence of toxic hepatitis in FUO patients was higher than that in non-FUO patients (89% vs. 50%, P < 0.05). Meanwhile, the misdiagnosis rate was considerably higher in the FUO group than in the non-FUO group (100% vs. 63%; P < 0.05). Conclusion Brucellosis is predominantly FUO admission in a non-endemic area of China, accompanied by irregular fever and toxic hepatitis. Careful examination of the epidemiological history and timely improvement of blood and bone marrow cultures can facilitate early diagnosis and prevent misdiagnosis.